Vanishing calcification associated with a spontaneous ventral spinal cerebrospinal fluid leak. (December 2016) - Schievink, Wouter I; Ross, Lindsey; Prasad, Ravi S; Maya, M Marcel
Background: Some patients with spontaneous intracranial hypotension have a ventral spinal cerebrospinal fluid (CSF) leak and these CSF leaks may be associated with calcified disk herniations. Identifying these calcifications is helpful in directing treatment. We report here the unusual case of a patient with a ventral CSF leak in whom the associated calcification absorbed over a five-month period. Case report: A 42-year-old woman developed orthostatic headaches and bilateral abducens nerve palsies. Magnetic resonance imaging of her brain showed typical findings of spontaneous intracranial hypotension. Magnetic resonance imaging of her spine showed an extensive cervicothoracic CSF leak. Computed tomographic myelography showed calcification at the Th1–2 disk space. Three epidural blood patches were performed, but her symptoms persisted. Digital subtraction myelography performed five months later showed an upper thoracic ventral CSF, but the calcification was no longer present. A dural tear, found at surgery at the Th1–2 level, was repaired and the patient made an uneventful recovery. Discussion: The resorption of calcifications at the level of a ventral spinal CSF leak could explain the absence of any calcifications in at least some patients with such leaks and demonstrates the usefulness of reviewing previous imaging in patients with ventral CSF leaks if the exact site of the leak remains unknown.